Undergraduate student´s values priorities as evidence of higher education for sustainable business, a cross-cultural study - Pérez Núñez, Sylvia Mónica; Zapletalováb, Šárka; Martínez Flores, Raúl; Woolfolk-Ruiz, Diana E.; Iqbale, Taskeen (My University, 2024)
This article explores the relationship between personal sustainable values and higher education for sustainable entrepreneurship in a cross-cultural context. It examines how values and academic training converge to promote sustainable business practices. To support this analysis, the value profiles of freshmen and senior students from Mexican and European universities were studied, highlighting the importance of values as a key component in educating sustainability-oriented business professionals. Empirical evidence shows that sustainability-related values become increasingly important as students advance in their education, particularly within cultural contexts prioritizing sustainable development. These findings underscore the relevance of this educational approach.
Keywords: Values; Higher education; Sustainable entrepreneurship; Sustainable education; Campus Tijuana